Faktor- Faktor Yang Mempengaruhi Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi - Vialeta, Nurul; Hizazi, Achmad; Prasetyo, Eko (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to analyze the influence of liquidity, profitability, capital structure, and firm size on firm value, with dividend policy as a moderating variable. The study focuses on consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. A total of 29 companies were selected using purposive sampling. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA). The findings show that liquidity and capital structure have no significant effect on firm value, while profitability and firm size have a significant positive effect. Additionally, dividend policy does not moderate the relationship between any of the independent variables and firm value. These results suggest that companies should focus on improving profitability and firm scale as key drivers of firm value, rather than relying on dividend policy to influence investor perceptions.